Future Figure of Agricultural Extension and Advisory Services - Kitahaka, Makoto (2021)
Makoto kitahaka SPECIAL EVENT UNFSS Independent Dialogue: The Critical Role of Agricultural Extension in Advancing the 2030 Agenda: Lessons from the Field and Empirical Evidence Co-Organized by IFPRI and Sasakawa Africa Association (SAA)